Manajemen Risiko dan Keberlanjutan Operasional Hotel di Tengah Ketidakpastian Ekonomi Global - Lidia Berliana Siboro (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to analyse how risk management contributes to the sustainability of hotel operations amid economic uncertainty. Unstable economic conditions affect the hospitality sector, making it important for hotel managers to identify, evaluate and manage risks effectively to maintain operational continuity. This research uses a qualitative approach with a case study method on several star-rated hotels in Medan City that are affected by economic uncertainty. Data were collected through in-depth interviews, as well as document analysis related to risk management and operational sustainability strategies implemented. The results showed that hotels that have a structured risk management system and are responsive to economic changes can survive better in the face of uncertainty. Strategies such as service diversification, efficient cost management, and technology utilisation in operations are the main keys to sustainability. This research contributes to hotel managers in developing best practices in risk management to face the challenges of a changing economy